Respuesta :
Answer:
v = 3(m1 - 2m2)/(m1 + m2)
Explanation:
Parameters given:
Velocity of first toy car with mass m1, u1 = 3 m/s (taking the right direction as the positive axis)
Velocity of second toy car with mass m2, u2 = -6 m/s (taking the left direction as the negative x axis)
Using conservation of momentum principle:
Total initial momentum = Total final momentum
m1*u1 + m2*u2 = m1*v1 + m2*v2
Since they stick together after collision, they have the same final velocity.
m1*3 + (m2 * -6) = m1*v + m2*v
3m1 - 6m2 = (m1 + m2)v
v = (3m1 - 6m2) / (m1 + m2)
v = 3(m1 - 2m2) / (m1 + m2)
Answer:
(2m1+3m2)/(m1+m2) m/s
Explanation:
From the law of conservation of momentum,
Total momentum before collision = Total momentum after collision
mu+m'u' =V (m+m').................... Equation 1
Where m = mass of the first toy car, m' = mass of the second toy car, u = initial velocity of the of the first toy car, u' = initial velocity of the second toy car, V = common velocity of the car after collision.
make V the subject of the equation above
V = (mu+m'u')/(m+m').............. Equation 2
Let the right be positive and the left be negative
Given: m = m1, m' = m2, u = 3 m/s, u' -6 m/s (left)
Substitute into equation 2
V = [(m1×2)-(m2×-3)]/(m1+m2)
V = (2m1+3m2)/(m1+m2) m/s